2015
DOI: 10.1097/jnr.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence Toward Emergency Department Staff in Jordanian Hospitals

Abstract: Policies and legislation related to workplace violence should be instituted and developed. Furthermore, EDS should be trained to deal with violent incidents and to understand violence management policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 1 publication
6
33
0
Order By: Relevance
“…These results were comparable to previous researches in Ghana [17], Egypt [18], Palestine [5], Turkey [19], Taiwan [4], Thailand [6], Iran [7], India [20] and Iraq [21]. A study on workplace violence toward emergency department staff in Jordanian hospitals similarly reported patients and their relatives as the main source of violence [22]. Our study participants cited communication gap between clients and nurses, delay in services due to understaffing, shortage of drugs and supplies as the key reasons provoking aggressions from patients and their escorts/relatives.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results were comparable to previous researches in Ghana [17], Egypt [18], Palestine [5], Turkey [19], Taiwan [4], Thailand [6], Iran [7], India [20] and Iraq [21]. A study on workplace violence toward emergency department staff in Jordanian hospitals similarly reported patients and their relatives as the main source of violence [22]. Our study participants cited communication gap between clients and nurses, delay in services due to understaffing, shortage of drugs and supplies as the key reasons provoking aggressions from patients and their escorts/relatives.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to our findings, this study indicates that the frustration that patients and their relatives may have to go through before they are attended to (due to long waiting times) and dissatisfaction with service could make them more inclined to abuse nurses verbally. A Jordanian study [22] similarly cited lack of resources, staff shortage and overcrowding as contributing factors to workplace violence in Jordanian hospitals. A study conducted in Egypt revealed comparable findings.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that perceptions of unit and institutional leadership support are related to nurses’ job satisfaction, intent to quit, and organizational commitment (Abou Hashish, ; Bobbio & Manganelli, ). Interestingly, items related to nurse‐patient or visitor interactions, such as using more frequent empathetic communication with patients or visitors (Lau, Magarey, & Wiechula, ), reducing unmet expectations (ALBashtawy et al., ; Angland, Dowling, & Casey, ), and interacting with patients or visitors presenting with behavioral health issues (Alameddine, Kazzi, El‐Jardali, Dimassi, & Maalouf, ; Gillespie et al., ), were underperformed and eliminated. Although this may be related to ENs’ reluctance to hold patients or visitors culpable for their behavior in certain circumstances and acceptance of PVV as part of the job (Copeland & Henry, ; Pourshaikhian et al., ), it may signify that organizational factors are significantly more important in making EN feel safe at work than patient or visitor interactions.…”
Section: Discussionmentioning
confidence: 99%
“…With that said, the healthcare sector is often reported to be one of the more at risk work environments (1), to the extent that workplace violence has begun to be seen as "just part of the job" by health care staff (3). Yet with almost 50% of surgical staff experiencing workplace violence (4), violence in medical workplaces has reached endemic levels (5)(6)(7)(8).…”
Section: Problemmentioning
confidence: 99%